Combination antiplatelet treatment in coronary artery disease patients: A necessary evil or an overzealous practice?. (3rd April 2018) - Alexopoulos, Dimitrios; Katogiannis, Konstantinos; Sfantou, Danai; Lekakis, John
Abstract: In seeking to improve care in coronary artery disease patients, further platelet inhibition has been occasionally applied beyond that provided by aspirin and a P2Y12 receptor antagonist. This review aims to offer insights about the rationale, the efficacy and safety of combination antiplatelet therapy, involving three or more agents. Overall, the use of glycoprotein (GP) IIb/IIIa inhibitors did not significantly modify the treatment effect of different antiplatelet strategies, including double vs standard clopidogrel, prasugrel vs clopidogrel, ticagrelor vs clopidogrel, cangrelor vs clopidogrel, and vorapaxar vs placebo. With the caveat that the use of GP IIb/IIIa inhibitor was not randomized, adding such an agent to aspirin and a P2Y12 receptor antagonist appears to carry a significantly increased bleeding potential. Moreover, adding vorapaxar to aspirin- and clopidogrel-treated patients is associated with more bleeding events, while the bleeding potential is further exacerbated in cases of quadruplicate antiplatelet treatment including aspirin, clopidogrel, vorapaxar, and a GP IIb/IIIa inhibitor. In ST-segment elevation, myocardial infarction patients' administration of an intravenous antiplatelet agent (GP IIb/IIIa inhibitor or cangrelor), in addition to aspirin and a P2Y12 receptor antagonist, efficiently bridges the pharmacodynamic gap of oral agents. Cilostazol on top of aspirin and clopidogrel appears to be safe, although of questionable clinical benefit. In conclusion, combination antiplatelet therapy should be reserved only for selected cases and following thoughtful consideration of the associated risk/benefit ratio.